1999
DOI: 10.1007/s002130050880
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of sexual behavior in male rats following d -amphetamine-induced behavioral sensitization

Abstract: The present study investigated the effect of sensitization, induced by repeated injections of d-amphetamine, on sexual behavior in the naive male rat tested in a drug-free state. Injections of either d-amphetamine (1.5 mg/kg, i.p.) or saline were given every other day for a total of ten injections, and this regimen induced behavioral sensitization of locomotor activity in drug-treated rats. After a 3-week post-drug period, d-amphetamine-treated rats exhibited facilitated sexual behavior, as indicated by shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
59
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 47 publications
9
59
1
Order By: Relevance
“…Indeed, preliminary observations from our laboratory indicate that rats sensitized by previous psychostimulant drug administration exhibit excessive cue-triggered reward-seeking behavior in this pure conditioned incentive paradigm (Wyvell and Berridge, 2000). These results are compatible with other evidence that sensitization increases the conditioned incentive value of reward-related stimuli (Harmer and Phillips, 1998;De Vries et al, 1999;Fiorino and Phillips, 1999;Taylor and Horger, 1999).…”
Section: Enhancement Of Incentive Salience Attributed To Cs؉supporting
confidence: 92%
“…Indeed, preliminary observations from our laboratory indicate that rats sensitized by previous psychostimulant drug administration exhibit excessive cue-triggered reward-seeking behavior in this pure conditioned incentive paradigm (Wyvell and Berridge, 2000). These results are compatible with other evidence that sensitization increases the conditioned incentive value of reward-related stimuli (Harmer and Phillips, 1998;De Vries et al, 1999;Fiorino and Phillips, 1999;Taylor and Horger, 1999).…”
Section: Enhancement Of Incentive Salience Attributed To Cs؉supporting
confidence: 92%
“…However, it is important to note that assessment of operant responding began one day after drug termination (when sensitization is not generally observed) and that the reduction in motivation was seen only during the first four days of amphetamine withdrawal. Other studies, using different conditioning procedures, have found evidence for crosssensitization between amphetamine and natural rewards such as food (Nocjar & Penksepp, 2002), salt (Clark & Bernstein, 2004), sucrose (Avena & Hoebel, 2003a, 2003bWyvell & Berridge, 2001) and sex (Fiorino & Phillips, 1999;Levens & Akins, 2004) 7-21 days after drug termination.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, evidence for cross sensitization between amphetamine and sex has been found in male rats (Fiorino & Phillips, 1999;Nocjar & Panksepp, 2002) and between cocaine and sex in male Japanese quail (Levens & Akins, 2004). In these studies, animals that exhibited behavioral sensitization to the drug exhibited more appetitive sexual behaviors than saline controls, despite the fact that they were in a drug free state at the time of testing.…”
mentioning
confidence: 99%
“…(Robinson and Becker, 1986;Stewart and Badiani, 1993)). Psychostimulant-induced behaviors, and associated biochemical changes, that may be related to bipolar disorder show sensitization in behavioral responses including hyperactivity (Post, 1980), stereotypy (Einat and Szechtman, 1995), increased hedonia (Papp et al, 1993), or increased sexual behavior (Fiorino and Phillips, 1999). However, oscillations have been shown only in very limited measures (e.g.…”
mentioning
confidence: 99%